Experimental Investigation of Flexural Behavior of Ultra-High-Performance Concrete with Coarse Aggregate-Filled Steel Tubes - Fanghong Wu (MDPI AG, 2021)
This paper presents an experimental investigation of flexural behavior of circular ultra-high-performance concrete with coarse aggregate (CA-UHPC)-filled steel tubes (CA-UHPCFSTs). A total of seven flexural members were tested under a four-point bending load. The failure modes, overall deflection curves, moment-versus-curvature relationships, moment-versus-strain curves, strain distribution curves, ductility, flexural stiffness and ultimate flexural capacity were evaluated. The results indicate that the CA-UHPCFSTs under bending behaved in a good ductile manner. The CA-UHPC strength has a limited effect on the ultimate flexural capacity, while the addition of steel fiber can improve the ultimate flexural capacity. Increasing the steel tube thickness leads to higher flexural stiffness and ultimate flexural capacity. There is a significant confinement effect between the steel tube and the CA-UHPC core in the compressive zone and centroidal plane after the specimen enters the elastic-plastic stage, while the confinement effect in the tensile zone is minimal. Moreover, the measured flexural stiffness and ultimate flexural capacity were compared with the predictions using various design specifications. Two empirical formulas for calculating the initial and serviceability-level flexural stiffness of CA-UHPCFSTs are developed. Further research is required to propose the accurate design formula for the ultimate flexural capacity of CA-UHPCFSTs.